Traditional knowledge of fishermen of the reproductive behavior of fish in a flood lake in western Pará, Brazil - Serrão, Elizabete de Matos; Braga, Tony Marcos Porto; Côelho, Yana Karine Silva; Campos, Diego Patrick Fróes; Santos, Anderson Araújo; Imbiriba, Luan Campos; Zacardi, Diego Maia (Sociedade & Natureza, 2019)
In this study we analyzed traditional knowledge that fishermen have of the reproductive behavior of the ten principal fish species that are captured in the region of Maicá, Santarém-Pará. Between March-December 2017 a total of 88 fisherman who have ten or more years of experience fishing in the region were interviewed using standardized and semi-structured forms. The knowledge possessed by fisherman in the region of Maicá was consistent among them and was also detailed and in agreement with concepts established in the scientific literature. Information related by the fishermen for which there were no theoretical references or that differed from the scientific literature can serve as a base for hypotheses for future studies in the region. We suggest that managers of fishing resources in the region take into consideration traditional local knowledge of these fishermen in the elaboration of management plans and future studies, and also apply it to the shared management plan of the future APA-Maicá once it is officially established and regulated.